Current practices for treatment of uterine fibroids - Shalini Singh; Tanmay Thulkar; Monisha Pawanarkar; Jyoti Thulkar (Wolters Kluwer Medknow Publications, 2017)
The treatment of uterine fibroids depends on symptoms of patients, size of the fibroid, desire for future pregnancy, and preference of the treating gynecologist. The present study was undertaken to compare treatment preferences in women desirous and nondesirous of pregnancy by an experienced gynecologist in symptomatic uterine fibroids. Newer medical or minimally invasive treatment modalities are increasingly being used for the treatment of fibroids. However, conventional surgical treatment such as myomectomy and hysterectomy are still preferred by gynecologists.